Kebijakan Hukum terhadap Problematika Pemberian Pemenuhan Hak Restitusi Korban Tindak pidana yang diatur KUHAP dan diluar KUHAP - Alyafedri, Youfan; Koto, Ismail (LPPM Universitas Ekasakti Padang, 2024)
Restitution is compensation given to the victim or their family by the perpetrator or a third party. Victims of criminal acts that can be given restitution are criminal acts of serious human rights violations, terrorism, human trafficking, racial and ethnic discrimination, criminal acts related to children, as well as other criminal acts determined by the LPSK Decree in accordance with the provisions of statutory regulations. . Of course, fulfilling the right to restitution for victims of criminal acts has several problems which are sometimes very detrimental to victims of criminal acts. Providing restitution still has not received attention from the government. It is still not balanced when compared with attention to perpetrators of criminal acts. The aim of this research is 1) to find out arrangements for providing restitution for victims of criminal acts. 2) to find out the implementation of providing restitution as a fulfillment of the rights of victims of criminal acts according to the KUHAP and outside the KUHAP, and 3) to find out the problems of giving the right to restitution to victims of criminal acts regulated by the KUHAP and outside the KUHAP. The method used is normative juridical research. The results of the research show that 1) Arrangements for providing restitution for victims of criminal acts have of course been regulated in the Criminal Procedure Code, namely in article 98, while outside the Criminal Procedure Code, regulations relating to restitution are regulated, one of which is stipulated in Supreme Court Regulation Number 1 of 2022. 2) Implementation of providing restitution in fulfillment of The rights of victims of criminal acts can be exercised in 2 ways, namely before the decision has permanent legal force and after the decision has permanent legal force. 3) The problem of granting restitution rights to victims of criminal acts is of course 3 factors, namely legal factors, law enforcement factors and community factors.